1981
DOI: 10.1093/jmedent/18.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and Humidity on Survival and Development of the Cat Flea, Ctenocephalides Felis (Siphonaptera: Pulicidae)

Abstract: The survival and development of the cat flea, Ctenocephalides felis, were assessed at various temperatures and relative humidities (RH). The upper and lower temperature limits for development (egg to adult) were 32 and 13 °C. The length of the developmental period ranged from 14 to 140 days at these temperature extremes. Complete development occurred from 50-92% RH. Immature C. felis reared at 92% RH produced larger adults than those reared at 50% RH. At 27 °C, the minimum RH necessary for greater than 50% sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 0 publications
2
57
0
2
Order By: Relevance
“…These studies have shown that flea egg and larval survival and development times increase with greater soil relative humidity (range ϭ 33-92%), and that dry soils (relative humidity Ͻ33%) are lethal to the larvae. 30 Flea reproductive success in the wild requires microsites with a relative humidity Ͼ 50%, and temperatures between 4ЊC and 35ЊC, 31 conditions that are commonly achieved in soils given sufficient precipitation. The ecology of cat fleas, however, differs from that of other flea species that typically transmit plague; e.g., cat fleas lay eggs in more exposed sites instead of rodent burrows, and do not occur in most plague-enzootic areas.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that flea egg and larval survival and development times increase with greater soil relative humidity (range ϭ 33-92%), and that dry soils (relative humidity Ͻ33%) are lethal to the larvae. 30 Flea reproductive success in the wild requires microsites with a relative humidity Ͼ 50%, and temperatures between 4ЊC and 35ЊC, 31 conditions that are commonly achieved in soils given sufficient precipitation. The ecology of cat fleas, however, differs from that of other flea species that typically transmit plague; e.g., cat fleas lay eggs in more exposed sites instead of rodent burrows, and do not occur in most plague-enzootic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The different climatic conditions in these areas, particularly with regard to temperature and humidity, may interfere with the biological cycles of the fleas in the two regions. Temperatures above 35 °C and below 3 °C and relative humidity less than 33% reduce the population of fleas in the environment (SILVERMANN et al, 1981;RUST, 1983). During the rainy season in Nanuque, the temperature is high (31 to 34 °C) and may not benefit the fleas, which are more prevalent in the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…Les résultats obtenus à partir de C. f. felis (Dryden, 1989 ;Silverman et al, 1991 ;Franc, 1998) indiquent que la durée de vie des individus à jeun des deux sousespèces de C. felis est semblable, quelle que soit la température. À 27 °c par exemple, Silverman et al (1991) ont montré que C. f. felis a un taux de survie de 10 %, six jours après l'émergence des adultes.…”
Section: Survie De C F Strongylus à Différentes Températuresunclassified